2000
DOI: 10.1364/ol.25.000445
|View full text |Cite
|
Sign up to set email alerts
|

Transform-limited spectral compression due to self-phase modulation in fibers

Abstract: We demonstrate near-transform-limited pulse generation through spectral compression arising from nonlinear propagation of negatively chirped pulses in optical fiber. The output pulse intensity and phase were quantified by use of second-harmonic generation frequency-resolved optical gating. Spectral compression from 8.4 to 2.4 nm was obtained. Furthermore, the phase of the spectrally compressed pulse was found to be constant over the spectral and temporal envelopes, which is indicative of a transform-limited pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
68
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 6 publications
0
68
0
Order By: Relevance
“…This method of spectral compression has been implemented using various types of fibres [5][6][7][8] and has also been studied in nonlinear waveguides [9]. It is suitable for a very large range of wavelengths including Ti:sapphire wavelengths [5,8], the widely used 1-m [7,10,11] and 1.55-m [12] windows and the emerging 2-m band [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method of spectral compression has been implemented using various types of fibres [5][6][7][8] and has also been studied in nonlinear waveguides [9]. It is suitable for a very large range of wavelengths including Ti:sapphire wavelengths [5,8], the widely used 1-m [7,10,11] and 1.55-m [12] windows and the emerging 2-m band [13].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the theoretical and experimental works to date have considered usual initial pulse profiles such as Gaussian or hyperbolic secant pulses [3,5,8,10,11,14]. However, several recent studies have demonstrated that the use of pre-shaped input pulses with a parabolic waveform can achieve spectral compression to the Fourier transform limit owing to the fact that for such pulses the cancellation of the linear and nonlinear phases can be made complete [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, the low optical nonlinearity of silica glass means that a significant nonlinear response at low pulse power can be obtained only after propagation through hundreds of meters of silica fiber. For many such applications chip-scale devices that integrate optical components to yield the desired functionality are preferable.…”
mentioning
confidence: 99%
“…Such spectral narrowing effect was first explained for a negatively-chirped optical pulse propagating in a normal dispersion optical fiber [1]. Chirped optical pulses within standard single-mode fiber [2] and photonic crystal fiber [3,4] were also capable of achieving spectral compression with a moderate spectral compression ratio (below 7). A comb-profiled fiber was used to demonstrate quasi-adiabatic soliton spectral compression [5].…”
Section: Introductionmentioning
confidence: 97%